IMPROVING STUDENTS' SPEAKING SKILLS THROUGH THE DESCRIBING METHOD (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The purpose of this research is to improve students speaking ability in English Learning, and does the use of the description method improve students speaking skills, of SMA Negeri 1 Pamanukan has been applied effectively in the classroom. Method of the Research this study was applyed in classroom action research. In the clssroom action research , the teacher gives action to students. New research planning, or research results have not been implemented. This study is entitled Imrpoving Students' Speaking Skills Through the Describing Method, using a descriptive method that aims to improve students' speaking skills using English.
Keywords: Improving; skill; speaking; describing; method